Weight Loss, Saline Loading, and the Natriuretic Peptide System - Arora, Pankaj (J Am Heart Assoc, 2015)
BACKGROUND: In epidemiologic studies, obesity has been associated with reduced natriuretic peptide (NP) concentrations. Reduced NP production could impair the ability of obese individuals to respond to salt loads, increasing the risk of hypertension and other disorders. We hypothesized that weight loss enhances NP production before and after salt loading. METHODS AND RESULTS: We enrolled 15 obese individuals (mean BMI 45±5.4 kg/m(2)) undergoing gastric bypass surgery. Before and 6 months after surgery, subjects were admitted to the clinical research center and administered a large‐volume intravenous saline challenge. Echocardiography and serial blood sampling were performed. From the pre‐operative visit to 6 months after surgery, subjects had a mean BMI decrease of 27%. At the 6‐month visit, N‐terminal pro‐atrial NP (Nt‐proANP) levels were 40% higher before, during, and after the saline infusion, compared with levels measured at the same time points during the pre‐operative visit (P<0.001). The rise in Nt‐pro‐ANP induced by the saline infusion (≈50%) was similar both before and after surgery (saline, P<0.001; interaction, P=0.2). Similar results were obtained for BNP and Nt‐proBNP; resting concentrations increased by 50% and 31%, respectively, after gastric bypass surgery. The increase in NP concentrations after surgery was accompanied by significant decreases in mean arterial pressure (P=0.004) and heart rate (P<0.001), and an increase in mitral annular diastolic velocity (P=0.02). CONCLUSION: In obese individuals, weight loss is associated with a substantial increase in the “setpoint” of circulating NP concentrations. Higher NP concentrations could contribute to an enhanced ability to handle salt loads after weight loss.